The Sex, Age, and Me study: recruitment and sampling for a large mixed-methods study of sexual health and relationships in an older Australian population - Lyons, A.; Heywood, W.; Fileborn, B.; Minichiello, V.; Barrett, C.; Brown, Graham; Hinchliff, S.; Malta, S.; Crameri, P. (Routledge, 2017)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. Older people are often excluded from large studies of sexual health, as it is assumed that they are not having sex or are reluctant to talk about sensitive topics and are therefore difficult to recruit. We outline the sampling and recruitment strategies from a recent study on sexual health and relationships among older people. Sex, Age and Me was a nationwide Australian study that examined sexual health, relationship patterns, safer-sex practices and STI knowledge of Australians aged 60 years and over. The study used a mixed-methods approach to establish baseline levels of knowledge and to develop deeper insights into older adult’s understandings and practices relating to sexual health. Data collection took place in 2015, with 2137 participants completing a quantitative survey and 53 participating in one-on-one semi-structured interviews. As the feasibility of this type of study has been largely untested until now, we provide detailed information on the study’s recruitment strategies and methods. We also compare key characteristics of our sample with national estimates to assess its degree of representativeness. This study provides evidence to challenge the assumptions that older people will not take part in sexual health-related research and details a novel and successful way to recruit participants in this area.